2022
DOI: 10.3389/fpubh.2022.1060284
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to organophosphate insecticides, inappropriate personal protective equipment use, and cognitive performance among pesticide applicators

Abstract: Inappropriate use of personal protective equipment (PPE) among pesticide applicators may increase urinary organophosphate (OP) metabolite levels and subsequently increase risks of cognitive performance. Therefore, this study aims to (1) compare urinary OP metabolite levels and cognitive performance between pre-and post-pesticide application seasons; (2) PPE use and factors associated with PPE use linked to increased urinary OP metabolite levels during pesticide application; and (3) the association between urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…Studies conducted earlier were on the impact of the use of PPE on the DAP metabolites in the urine, but in the present study, an attempt was made to assess differences between commercially available PPE and the PPE prepared using the available resources, which could serve as a reference and may be one of its kind to the best of our knowledge as a part of the second phase of the intervention and could not be compared with any other studies because of lack of availability of the epidemiological data on the same. Overall, the present study findings demonstrate the minimization of OP exposure followed by reduction in DAP metabolite concentrations in urine samples among farmworkers when they have used PPE provided to them, which is in agreement with another study done elsewhere, indicating that the inadequacy or nonuse of PPE during pesticide application was the main factor impacting urine OP metabolite levels, and using adequate PPE such as gloves and a mask while handling pesticides is a significant variable in limiting occupational exposure to OPs 23 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Studies conducted earlier were on the impact of the use of PPE on the DAP metabolites in the urine, but in the present study, an attempt was made to assess differences between commercially available PPE and the PPE prepared using the available resources, which could serve as a reference and may be one of its kind to the best of our knowledge as a part of the second phase of the intervention and could not be compared with any other studies because of lack of availability of the epidemiological data on the same. Overall, the present study findings demonstrate the minimization of OP exposure followed by reduction in DAP metabolite concentrations in urine samples among farmworkers when they have used PPE provided to them, which is in agreement with another study done elsewhere, indicating that the inadequacy or nonuse of PPE during pesticide application was the main factor impacting urine OP metabolite levels, and using adequate PPE such as gloves and a mask while handling pesticides is a significant variable in limiting occupational exposure to OPs 23 …”
Section: Discussionsupporting
confidence: 92%
“…Overall, the present study findings demonstrate the minimization of OP exposure followed by reduction in DAP metabolite concentrations in urine samples among farmworkers when they have used PPE provided to them, which is in agreement with another study done elsewhere, indicating that the inadequacy or nonuse of PPE during pesticide application was the main factor impacting urine OP metabolite levels, and using adequate PPE such as gloves and a mask while handling pesticides is a significant variable in limiting occupational exposure to OPs. 23 However, the results of the present study should be considered in light of its limitations. Although 24-hour voids provide more and complete information on the data collection, in the present study, the urine sample collection involved first-void samples, as the 24-hour void method is very onerous on participants, which may impact their level of participation, and hence, creatinine-corrected concentrations were used to reduce variability.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…PPE use during pesticide dissemination is recommended among farmworkers for protection as the chemical substances of pesticides can enter the human body through inhalation, as well as oral and skin routes. Chittrakul et al, 39 found that inappropriate use of PPE may elevate urinary organophosphate metabolite levels.…”
Section: Characteristics and Pesticide Use Behavior Associated With C...mentioning
confidence: 99%